A Nanogenerator Enabled by a Perfect Combination and Synergetic Utilization of Triboelectrification, Charge Excitation and Electromagnetic Induction to Reach Efficient Energy Conversion. (17th January 2023) - Li, Gui; Wang, Jian; Fu, Shaoke; Shan, Chuncai; Wu, Huiyuan; An, Shanshan; Du, Yan; He, Wencong; Wang, Zhao; Liu, Wenlin; Nie, Yongjie; Liu, Siyang; et al.
Abstract: Triboelectric–electromagnetic hybridized nanogenerator (TEHG) is confirmed as an effective energy harvesting for Internet of Things. However, it is still a great challenge to gain a high‐output triboelectric‐nanogenerator (TENG) and to perfectly combine TENG with electromagnetic generator (EMG). Herein, a TEHG composed of space confined multi‐layer‐stack TENG (SM‐TENG) and stack compression promoted flux change EMG is proposed. The interaction of magnets on the rotor with the magnets on the stator makes contact–separation of the SM‐TENG and changes the magnetic flux of EMG in rotation process, reducing wear and deformation of TENG. A voltage multiplier circuit (VMC) with a Zener diode is employed to enhance SM‐TENG performance and maintain stable output. The output charge and current of four SM‐TENG units reach 3.2 µC and 385 µA at rotatory speed 60 rpm, and the voltage of four EMG reaches 8.09 V. The perfect combination and synergetic utilization of triboelectrification, charge excitation, and electromagnetic induction in a single device are realized. The integrated TEHG can power 12 bulbs (2 W) and 16 thermo‐hygrometers, and a Bluetooth thermo‐hygrometer to transmit wireless signals to a mobile phone. This work provides a new strategy for high efficient integration and utilization various mechanisms in one energy‐harvesting device. Abstract : The TEHG device integrated on VMC and PMM is proposed to improve the output performance of TENG part and efficiently combined with EMG for constructing a power supply device by harvesting mechanical energy.